The Influence of E-Commerce and Social Media on Revenue Growth Moderated by Production Costs in Micro, Small, and Medium Enterprises (MSMES) - Dimas Arya Kusuma; Munari Munari (Yayasan Riset dan Pengembangan Intelektual, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) play a vital role in Indonesia's economy, yet many of them risked bankruptcy during the COVID-19 epidemic. This study aims to analyze the impact of social media and e-commerce on MSME income with the moderation of production costs. A quantitative descriptive approach was employed in this study to analyze the data obtained from the research instrument, a questionnaire. The approach included tests for validity, reliability, normality, autocorrelation, multicollinearity, heteroscedasticity, moderation regression analysis (MRA), F and t statistical tests, and the coefficient of determination test (R2). The results show that e-commerce and social media do not have a significant individual impact on increasing MSME income, and production costs do not moderate this relationship. The implications of this study highlight the importance of effective production cost management to maximize the benefits of digital technology in increasing MSME income. This study recommends expanding the sample scope and using mixed methods for more in-depth analysis in the future.